Volume 1: Turbomachinery 1988
DOI: 10.1115/88-gt-70
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D Navier Stokes Solver for Application to all Types of Turbomachinery

Abstract: This paper describes the current stage of development of a code aimed at solving the 3D Navier-Stokes equations in any type of turbomachinery geometry. The basic algorithm time marches the fully 3D unsteady equations of motion expressed in finite volume form with a two step explicit / one step implicit method. Full multigrid acceleration is used to reduce solution time and maintain code performance on fine meshes. Turbulence modelling is via mixing-length closure and the widely used Baldwin-Lomax model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
87
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 6 publications
2
87
0
Order By: Relevance
“…To validate the laser measurements, velocity profiles calculated from total pressure measurements in the vaneless diffuser are presented and compared to those measured using laser anemometry. The measurements are supported further by a BTOB3D code (Dawes, 1988) analysis which predicts a flow field that is similar to the one that was measured and shows the origin of the flow features that were observed.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…To validate the laser measurements, velocity profiles calculated from total pressure measurements in the vaneless diffuser are presented and compared to those measured using laser anemometry. The measurements are supported further by a BTOB3D code (Dawes, 1988) analysis which predicts a flow field that is similar to the one that was measured and shows the origin of the flow features that were observed.…”
Section: Introductionsupporting
confidence: 49%
“…The depth and location of the wake zone appears to have been modified by the amount of blade backsweep that was applied at the impeller exit. Hathaway et al (1993) obtained detailed measurements of the secondary flow fields in a large-low-speed impeller and compared them to the results of a 3D Navier-Stokes simulation using the BTOB3D code (Dawes, 1988). This work suggested that the origin of the low momentum fluid may lie in a vortex which is formed by the interaction of a tip clearance jet with the centrifuged suction surface boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The Dawes code uses the Baldwin-Lomax mixing length turbulence model. The reader is referred to Dawes (1986Dawes ( , 1987Dawes ( , and 1988) for more information on the particulars of the three-dimensional code. This particular code was chosen by the author because of its robustness and stability.…”
Section: Introductionmentioning
confidence: 99%
“…This particular code was chosen by the author because of its robustness and stability. It is widely used in the turbomachinery industry (Dawes 1988;Casey, et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficiency of a partial admission stage, experimental studies of partial admission turbines have been made (1) . Although studies using CFD analysis, which is often applied to other turbomachinery (2) , are rare because it requires heavy computational load due to unsteadiness and full circle modeling (3) . It is difficult to carry out unsteady analysis of fully 3-dimensional partial admission stages in a short period of time at practical costs, although computers have been making great progress in this decade.…”
Section: Introductionmentioning
confidence: 99%